1999
DOI: 10.1111/j.1528-1157.1999.tb02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Referral Patterns of Family Physicians May Allow Population‐Based Incidence Studies of Childhood Epilepsy

Abstract: Summary:Purpose: To evaluate the burden of illness of childhood epilepsy on patient, care giver, and society, representative incidence cohorts must be followed longitudinally. Case ascertainment through pediatricians and neurologists would be a valid method if family physicians refered all new cases of childhood epilepsy. The study objective was to determine whether family physicians' referral patterns in Southwestern Ontario make it possible to conduct a population-based incidence study of childhood epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…However, there are feasibility constraints in designing population-based studies. In the absence of population-based registries for epilepsy to facilitate such studies, Speechley et al [41] demonstrated that it may be feasible to recruit a representative population-based sample of children with epilepsy by targeting pediatric neurologists. In this study, family physicians practicing in southwestern Ontario reported they would refer between 80 and 99% of their patients with childhood epilepsy (depending on the type of seizure and syndrome) to a pediatric neurologist.…”
Section: Discussionmentioning
confidence: 98%
“…However, there are feasibility constraints in designing population-based studies. In the absence of population-based registries for epilepsy to facilitate such studies, Speechley et al [41] demonstrated that it may be feasible to recruit a representative population-based sample of children with epilepsy by targeting pediatric neurologists. In this study, family physicians practicing in southwestern Ontario reported they would refer between 80 and 99% of their patients with childhood epilepsy (depending on the type of seizure and syndrome) to a pediatric neurologist.…”
Section: Discussionmentioning
confidence: 98%
“…A longer study period would have likely shown a much higher neurologist visit rate. In fact, a prior Canadian study found that over 80% of the children with epilepsy are referred to a neurologist (Nixon Speechley et al, 1999). In addition, only prevalent cases were used.…”
Section: Discussionmentioning
confidence: 99%
“…Employing population-based sampling procedures that include multiple sites will facilitate the recruitment of a representative sample of the pediatric epilepsy population. 24 Furthermore, researchers interested in HRQL should avoid restricting their samples based on child characteristics, particularly those relating to intellectual or cognitive ability. Despite the high prevalence of cognitive deficit among children with epilepsy, 25 over half of the studies included in this meta-analysis excluded such children.…”
Section: Summary Of Findingsmentioning
confidence: 99%